Leaf Stomatal Characteristics of Some Species in Bush Form Used in Kastamonu Urban Landscape - YİĞİT, Nurcan; GEDİKOĞLU, Nurcihan Esra; ÖZTÜRK PULATOĞLU, Ayşe (Kent Akademisi, 2022)
Nowadays, the rapidly increasing population has brought many problems such as building concrete structures everywhere, air pollution, and traffic congestion. It is known that parks and gardens, which are an important element for the urban landscape, not only balance the human-nature relationship in cities, but also improve urban living conditions. Parks and gardens that utilize urban areas in a functional and aesthetic way to meet the recreational needs of people, to recover the lost nature and to create healthy living spaces are extremely important. In this study, it was aimed to determine the leaf stomatal characteristics of Buxus microphylla Siebold & Zucc., Prunus laurocerasus L, Ligustrum delavayanum Har., Berberis thunbergii DC., Ilex aquifolium L., Euonymus japonicus Wall. var. aureomarginatus Rehder, Cotoneaster lacteus W.W.Sm., Mahonia aquifolium (Pursh) Nutt., Pyracantha coccinea M. Roem. species, one of the species used in the park, garden and central landscaping studies in Kastamonu province. With micromorphological investigations, stomatal characteristics were determined by SEM on the species used in the study. With respect to stomatal density in the unit area on species, it was determined that Pyracantha coccinea species had the maximum stomatal density (81) while Cotoneaster lacteus species had the minimum stomatal density (10). Furthermore, it was determined that Prunus laurocerasus (34.82 µm) had mean the longest stomatal length and Mahoni aquifolium (7.183 µm) had the mean shortest stomatal length.
Keywords: Kastamonu; micromorphological characteristic; SEM; stoma; Çevre Bilimleri; Kastamonu; Mikromorfolojik Karakterler; SEM; stoma; Peyzaj Mimarlığı; Landscape Architecture; Environmental Sciences; 13. Climate action; 11. Sustainability; 15. Life on land